2021
DOI: 10.1002/aet2.10712
|View full text |Cite
|
Sign up to set email alerts
|

Defining well‐being: A case‐study among emergency medicine residents at an academic center: A qualitative study

Abstract: Background Healthcare‐associated burnout is linked to reduced quality of care, decreased patient experience, and higher cost. The National Academy of Medicine has emphasized the importance of supporting clinician well‐being across healthcare; however, well‐being is poorly defined, especially early in emergency medicine training. Objectives The primary objective of this study was to explore and understand the attitudes, beliefs, and perspectives of emergency medicine (EM) resident physicians surrounding well‐be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This study found that, regardless of whether students had already witnessed the care of a critically ill patient, most students did not feel prepared to identify or address the emotional impact associated with these situations. This highlights the need to train students early and normalize the emotional impact of working in medicine [19,20]. The stigma associated with mental health in health care has pervaded the classroom and hospitals, and to build structures to prevent burnout, we must begin early to help trainees identify feelings of anxiety, depression, or stress as they experience them [13,[21][22][23].…”
Section: Principal Findingsmentioning
confidence: 99%
“…This study found that, regardless of whether students had already witnessed the care of a critically ill patient, most students did not feel prepared to identify or address the emotional impact associated with these situations. This highlights the need to train students early and normalize the emotional impact of working in medicine [19,20]. The stigma associated with mental health in health care has pervaded the classroom and hospitals, and to build structures to prevent burnout, we must begin early to help trainees identify feelings of anxiety, depression, or stress as they experience them [13,[21][22][23].…”
Section: Principal Findingsmentioning
confidence: 99%
“…Alternatively, a study examining different types of stressors in a simulated clinical environment may use heart rate variability to assess objective physiologic response to stressors and a survey instrument to assess trainees' subjective perceptions of stress 2 . Additionally, qualitative methodologies are often ideally suited to deeply explore poorly understood or poorly defined concepts, such as physician shame 3 . Ultimately, the prospective survey designer should carefully consider the strengths and limitations of using a survey as a research tool.…”
Section: Is a Survey The Right Tool?mentioning
confidence: 99%
“…2 Additionally, qualitative methodologies are often ideally suited to deeply explore poorly understood or poorly defined concepts, such as physician shame. 3 Ultimately, the prospective survey designer should carefully consider the strengths and limitations of using a survey as a research tool.…”
Section: Is a Surve Y The Ri G Ht Tool?mentioning
confidence: 99%
See 1 more Smart Citation